Myocardial perfusion quantification by CMR for detection of obstructive coronary artery disease in patients with previous coronary artery bypass surgery. (13th July 2021) - Franks, R; Milidonis, X; Morgan, H; Ryan, M; Perera, D; Plein, S; Chiribiri, A
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): British Heart Foundation Background: Coronary artery bypass grafting (CABG) is an established treatment for patients with advanced coronary artery disease (CAD). A subsequent recurrence of symptoms can cause the need for re-assessment of the coronary circulation. The accuracy of visually assessed stress perfusion cardiovascular magnetic resonance (CMR) for the detection of obstructive CAD is reduced in patients with prior CABG. In patients with complex multi-vessel CAD, myocardial perfusion quantification by CMR is superior to visual assessment (VA) for detection of obstructive disease however patients with CABG have been absent from previous studies. Purpose: This study sought to assess the performance of myocardial perfusion quantification by CMR against invasive coronary angiography (ICA) for detecting obstructive CAD in patients with previous CABG. Methods: Twenty-nine patients with a history of previous CABG and subsequent clinically indicated perfusion CMR study and invasive coronary angiography were recruited. Patients underwent a dual bolus stress perfusion CMR with late gadolinium enhancement (LGE) imaging at 3 Tesla. Stress myocardial blood flow (MBF) was estimated at the coronary territory level according to the AHA 16 segment model using Fermi function-constrained deconvolution. Segments with transmural LGE were excluded from MBF analysis. Stress perfusion images were analysed visually alongside LGE images and matched perfusion-LGE defects were considered negative. On ICA, coronary territories with lumen stenosis >70% without an unobstructed bypass graft (<70% stenosis) were considered positive. Results: 86/87 coronary territories were suitable for analysis. Sixty-five territories had at least one bypass graft including 32 territories with arterial grafts. 28/86 territories (33%) had obstructive disease on angiography. Territories with obstructive CAD had significantly lower stress MBF than unobstructed territories (1.21 [IQR: 0.96–1.45] vs 1.58 [1.40–1.84] ml/g/min, p < 0.001, Figure 1). Stress MBF had good accuracy to detect coronary territories with obstructive CAD (sensitivity 71%, specificity 84%, area under the curve (AUC) 0.83, p < 0.001, Figure 2A). For visual assessment, sensitivity was 79%, specificity 78% and diagnostic accuracy 78%. When analysis was confined to only territories with bypass grafts, stress MBF had 78% sensitivity, 81% specificity and AUC of 0.85, p < 0.001 (Figure 2B).. In this subgroup, VA had a sensitivity of 78%, specificity of 76% and a 77% diagnostic accuracy. Conclusions: In patients with previous surgical revascularisation, quantification of stress myocardial blood flow by CMR offers good diagnostic accuracy for the detection and localisation of anatomically significant stenoses. Accuracy is reduced compared with published data in patients without coronary grafts but remains comparable to expert visual assessment.